Paediatric to Adult Transition of Care in IBD: Understanding the Current Standard of Care Among Canadian Adult Academic Gastroenterologists. Issue 6 (3rd August 2019) - Jawaid, Noor; Jeyalingam, Thurarshen; Nguyen, Geoffrey; Bollegala, Natasha
Abstract: Background: The optimal form of health care delivery for paediatric to adult inflammatory bowel disease transition of care is unknown. The primary purpose of this study was to establish current standard of care across Canada among adult gastroenterologists. Methods: Adult gastroenterologists interested in transition care were identified. Twenty-five anonymous surveys and 17 semistructured interviews representing 9 adult gastroenterology centers across 6 provinces were completed. Questions focused on the transition process, referral practices, information transfer and access to multidisciplinary resources. The need for expert guidance and transition-related quality indicators were identified. The interviews were audio-recorded, transcribed and coded in duplicate for qualitative thematic analysis. Results: Transition practices included the following: transition clinic ( n = 4) versus direct transfer ( n = 5). Most transition patients were referred to academic centers. Transfer volume per center ranged from 12 to 100 per year. Transfer of information was optimized with shared electronic medical record and comprehensive referral package. The majority of the programs lacked consistent access to a multidisciplinary team. The strongest attributes related to health care provider interest in transition and complete information transfer. Areas for improvement included increased resource allocation: financial, logistical and personnel. All agreed that a consensus-based guidfmeline for adult phase of transition would be beneficial. Potential quality indicators included adherence to care, depression/anxiety scores and patient knowledge. Conclusions: This Canadian study of adult gastroenterologists revealed that while practice patterns vary, most agree that a transition clinic with access to multidisciplinary resources would be beneficial. A consensus-based guideline and quality indicators to assess performance may standardize the adult phase of transition and optimize outcomes.